Strategi Sosialisasi Perpajakan Atas Transaksi E-Commerce Pada UMKM Pada UMKM (Studi Kasus Pada KPP Jakarta Pademangan) - Ayu Silviani Dewi; Bambang Irawan (Jurnal Ilmu Administrasi Publik, 2023)
The number of e-commerce transactions in indonesia from year to year has always increased. With the increase of e-commerce transactions in Indonesia with the number of taxpayers also increased. The increase in the number of taxpayers must be balanced with taxpayer compliance in paying taxes. The purpose of this study is to examine the strategy of socialization of taxation on e-commerce transactions in MSMEs at the Tax Office Pratama Pademangan. The method used in this study is a qualitative method with data collection techniques conducted by the method of interviews, observation and documentation, with six speakers, namely two e-commerce business taxpayers, two representatives of the supervision and consultation section of the Tax Office Pratama Pademangan, and two from the stiami Institute academics. The results of this study indicate that the socialization of taxes through social media, news on social media held events, community involvement, approach through whatsapp and door to door have a positive effect on taxpayer awareness and compliance e- commerce actors in paying tax obligations on e-commerce transactions in MSMEs. While the socialization strategy of identity inclusion has no influence on taxpayer compliance of e-commerce businesses in MSMEs.